Enhancing surface quality of en31 steel using Taguchi robust design - Fayaz Ahmad Mir; Sheikh Shahid Ul Islam; Mohammad Irfan Hajam; Lubaid Nisar (International Journal of Engineering and Technology, 2023)
This study employs Taguchi's robust design and regression to investigate how milling process parameters affect EN31 steel machin-ability. Three parameters—cutting speed, feed per tooth, and depth of cut—underwent nine experiments using Taguchi's L9 or-thogonal plan on a CNC milling center. Optimal settings were determined through mean analysis (ANOM), while analysis of vari-ance (ANOVA) with 95% confidence assessed parameter impact on surface roughness. Notably, feed per tooth displayed substantial influence (75.351%) on surface roughness. Regression analysis effectively aligned predictions with experimental outcomes, and a confirmation test validated successful Taguchi optimization.